Uncovering the effect and mechanism of Panax notoginseng saponins on metabolic syndrome by network pharmacology strategy. (10th January 2023) - Wang, Yisa; Ma, Peng; Wang, Zijing; Sun, Mingxia; Hou, Biyu; Xu, Tianshu; Li, Wenlan; Yang, Xiuying; Du, Guanhua; Ji, Tengfei; Qiang, Guifen
Abstract: Ethnopharmacological relevance: Metabolic syndrome (MetS) is a cluster of disease centered on obesity, which is the result of stagnation of liver qi according to traditional Chinese medicine. P anax notoginseng is a traditional Chinese herbal medicine, entering liver and stomach meridians and dissipating blood stasis, in which panax notoginseng saponins (PNS) are the main active components. However, its effects and mechanism on metabolic syndrome has not been revealed yet. Aim of study: To evaluate the anti-MetS effect of PNS, including body weight and adiposity, glucose metabolism and non-alcoholic fatty liver disease (NAFLD), as well as to explore the mechanism and signaling pathway of PNS on MetS effect. Materials and methods: HPLC was utilized to affirm the percentages of saponins in PNS. In vivo, normal C57BL/6J mice and high-fat diet (HFD)-induced MetS mice were used to evaluate anti-MetS effect of PNS. Body weight, food and water intake were recorded. NMR imager was used for NMR imaging and lipid-water analysis. Blood glucose detection, glucose and insulin tolerance test were performed to evaluate glucose metabolism. Biochemical indexes analysis and histopathological staining were used to evaluate the effect on NAFLD. The expressions of mRNA and proteins related to thermogenesis in adipose tissue were determined using real-time PCR and Western blot. In silico, network pharmacology was utilized to predict potential mechanism. In vitro, matured 3T3-L1 adipocyte was used as subject to confirm the signaling pathway by Western blot. Results: We determined the content of PNS component by HPLC. In vivo, PNS could improve metabolic syndrome with weight loss, reduction of adiposity, improvement of adipose distribution, correction of glucose metabolism disorder and attenuation of NAFLD. Mechanismly, PNS boosted energy exhaustion and dramatically enhanced thermogenesis in brown adipose tissue (BAT), induced white adipose tissue (WAT) browning. In silico, utilizing network pharmacology strategy, we identified 307 candidate targets which were enriched in MAPK signaling pathway specifically in liver tissue and adipocyte. In vitro validation confirmed ERK and p38MAPK mediated anti-MetS effects of PNS, not JNK signaling pathway. Conclusion: PNS exerted protective effect on metabolic syndrome through MAPK-mediated adipose thermogenic activation, which may serve as a prospective therapeutic drug for metabolic syndrome. Graphical abstract: Image 1